Global Hippocampal Volume Reductions and Local CA1 Shape Deformations in Amyotrophic Lateral Sclerosis - Machts, Judith; Vielhaber, Stefan; Kollewe, Katja; Petri, Susanne; Kaufmann, Joern; Schoenfeld, Mircea Ariel (Frontiers in Neurology, 2018)
There is increasing evidence for hippocampal involvement in Amyotrophic Lateral Sclerosis (ALS). Recent neuroimaging studies have been focused on disease-related hippocampal volume alterations while changes in hippocampal shape have been investigated less frequently. Here, we aimed to characterize the patterns of hippocampal degeneration using both an automatic and manual volumetric and surface-based approach in a group of 31 patients with ALS and 29 healthy controls. Irrespective of the segmentation type, left and right hippocampal volumes were significantly reduced in ALS compared to controls. Local shape alterations were identified in the hippocampal head region of patients with ALS that corresponds to the cornu ammonis field 1 (CA1), a region known to be involved in novelty detection, memory processing, and integration of hippocampal input and output information. The results suggest a global hippocampal volume loss in ALS that is complemented by local shape deformations in a highly interconnected region within the hippocampus.